Synthesis and Characterization Palladium(II) Complexes of benz-1,3-imidazoline-2-thione, benz-1,3-thiazoline-2thione and Diamine Ligands - Ahmed, Shihab A. O. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Reaction of Na2PdCl4 with benz-1,3-imidazole-2-thione or (bzimtH) benz-1,3-thiazoline2-thione (bztztH) in ethanol / NE3 afford complexes of the type [Pd(bzimt)2](1) and [Pd(bztzt)2](2) respectively. Treatment of [Pd(L)2] L= bzimt or bztzt with bidentate ligands (N^N) where N^N= bipyridine (Bipy) , phenanthroline (Phen) , ethylene diamine , or N,N′dimethylethylene diamine afford mononuclear complexes of the type [PdL2(N^N)]. The bzimt and bztzt ligands are coordinated as bidentate chelating ligands through the S and N in (1) and (2) whereas bonded as a monodentate fashion via the sulfur atom in other complexes. The prepared complexes were characterized by elemental CHN analysis, ir and 1H nmr spectra.